Effects of Sub-threshold Transcutaneous Auricular Vagus Nerve Stimulation on Cingulate Cortex and Insula Resting-state Functional Connectivity - Mao, Yixiang; Chen, Conan; Falahpour, Maryam; MacNiven, Kelly H.; Heit, Gary; Sharma, Vivek; Alataris, Konstantinos; Liu, Thomas T. (Frontiers in Human Neuroscience, 2022)
Transcutaneous auricular vagus nerve stimulation (taVNS), a non-invasive alternative to vagus nerve stimulation (VNS) with implantable devices, has shown promise in treating disorders such as depression, migraine, and insomnia. Studies of these disorders with resting-state functional MRI (rsfMRI) have found sustained changes in resting-state functional connectivity (rsFC) in patients treated with low frequency (1 to 20 Hz) taVNS. A recent study has reported reductions in pain scores in patients with rheumatoid arthritis after a 12-week treatment of high-frequency (20 kHz) sub-threshold taVNS. However, no studies to date have examined the effects of high-frequency sub-threshold taVNS on rsFC. The objective of this study was to determine whether high-frequency sub-threshold taVNS induces changes in rsFC using seed regions from the cingulate cortex and insula, brain regions that play a key role in interoception and processing of pain. With a single-blind placebo-controlled repeated measures experimental design, rsfMRI scans were acquired before and after 15 minutes of either sub-threshold taVNS treatment or a sham control. Significant taVNS-related changes in functional connections to the cingulate cortex were detected between the anterior cingulate cortex and right superior temporal gyrus and between the midcingulate cortex and right inferior parietal lobule. In addition, significant changes in functional connections to the insula were detected between the posterior insula and right precuneus and between the anterior insula and right cuneus gyrus. These results suggest that high-frequency sub-threshold taVNS can lead to sustained effects on rsFC of brain regions involved in interoception and processing of pain in a cohort of healthy subjects. This study lays the foundation for future rsfMRI studies of high-frequency sub-threshold taVNS in clinical populations.